Barbara Tirone, Elena Cogato Lanza, Luca Pattaroni, Mischa Piraud (eds), De la différence urbaine. Le quartier des Grottes / Genève, Genève, Métis Presses, series: vuesDensemble, 2013 - Matera, Giovanni (PARTECIPAZIONE E CONFLITTO, 2014)
No Abstract is required for Book Reviews